Pengaruh Kualitas Pelayanan Unit Aviation Security terhadap Kepuasan Penumpang pada Bandara Domine Eduard Osok Kota Sorong - Takaselumang, Mauren; Kastanya, James; Jantje, Hendry J. (Attractive : Innovative Education Journal, 2022)
This study aims to influence the quality of services to analyse the aviation security to the satisfaction of passengers at the airport domine eduard osok. Sorong city. The method of analysis the data used was descriptive analysis quantitative. Testing significant through (uji-t), using simple linear regression and coefficients determinansi (r).The population of the research is the employees eduard osok. domine airport. Respondents were 30 sample .The primary data was obtained through interviews , and study the documentation .Of the results of data processing linear regression analysis on the simple spss for windows version he obtained the regression equation is 25 = 11,019 + 0,695x , the regression coefficient 0,683 that will each contain changes and adding one percent on the quality of services and the satisfaction 0,695 passengers will be increased by a zero sum if the variable quality of services , so passengers has value of 11.019 satisfaction .On the coefficients determined obtained r % 58.6 square . It means the quality of services led to the satisfaction of passengers is 58.6 % . The remaining 41.4 % influenced by other factors are not in analysis in this research. The results of the t, where thitung 6.291 & gt; of ttabel 1.7011 it can be said that variebel the quality of services have had a positive impact and significant impact on satisfaction passengers. Keywords: Service Quality, Management Quality, Aviation Security